REKONSTRUKSI SISTEM PENYELENGGARAAN PASAR MODAL SYARIAH - Salsabila Nadhifa; Nabitatus Sa’adah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
The capital market that is widely used by people is not in accordance with the provisions contained in sharia principles. Therefore, a capital market with sharia. Conventional capital markets and Islamic capital markets have a similar concept but differ in principles and have different types of contracts. This difference between conventional capital market principles and the principles contained in the Islamic capital market results in the need for regulations that specifically regulate the Islamic capital market. so it is necessary to update the Law No. 8 of 1995 concerning Capital Markets. Judging from the legal system, the Sharia Capital Market still has weaknesses related to the legal substance, legal structure and legal culture so that reconstruction of Islamic capital market regulations must be conducted. The method used in this writing is analytical descriptive and uses a normative juridical approach.